2003
DOI: 10.1159/000069833
|View full text |Cite
|
Sign up to set email alerts
|

Intrapericardial Instillation of Mitoxantrone in Palliative Therapy of Malignant Pericardial Effusion

Abstract: Background: Pericardial effusions occurring with pericardial or myocardial metastases often cause serious complications, necessitating temporary or emergency relief by percutaneous pericardiocentesis. However, this often results in recurrences. For long-term therapy success, the intrapericardial instillation of anti-neoplastic agents is an alternative to surgical methods, which are stressful for the patient. Following our positive experiences with mitoxantrone in the treatment of malignant pleural effusions, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Of the underlying primary tumours, 36.5% are lung cancer [12]. The pericardial tumour spread causes typically malignant pericardial effusion (MPE).…”
Section: Pericardial Effusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the underlying primary tumours, 36.5% are lung cancer [12]. The pericardial tumour spread causes typically malignant pericardial effusion (MPE).…”
Section: Pericardial Effusionmentioning
confidence: 99%
“…Carboplatin [22], cisplatin [23] or mitoxantrone [12] for example can be used for intrapericardial instillation to achieve control of refractory pericardial effusion.…”
Section: Pericardial Effusionmentioning
confidence: 99%
“…nitrogen mustard, mitomycin C, mitoxantrone, 5-fluorouracil, but only case reports or small series have been published, making it impossible to judge the response rates [57,[115][116][117] . Musch et al [118] in 2003, reported 12 complete remissions and 3 partial remissions (small pericardial effusion) among 16 patients (8 bronchial, 7 breast, 1 stomach carcinoma) treated with 10-20 mg of mitoxantrone left in the pericardium for 24 h; the follow-up lasted 28-730 d (mean 6 mo). In a multicenter series of various tumors, the mean effusion-free period of the patients treated with local chemotherapy (various agents) was 372 d (median 223 d); at 1, 2, 6 and 12 mo, 58%, 52%, 33% and 16%, respectively, were completely effusion-free.…”
Section: Local Chemotherapymentioning
confidence: 99%
“…Most previous studies involving mitoxantrone have included mixed study populations with a wide array of primary cancers and/or different intracavitary sites (pleural, peritoneal, or pericardial) for pleurodesis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Only a few, thus far, have focussed specifically on a select group of neoplasms of interest, such as breast cancer (20), ovarian cancer (2), or metastatic sarcoma (21), but not lung cancer.…”
Section: Introductionmentioning
confidence: 99%